PHILOLOGY AS THE ART OF UNDERSTANDING - Irgasheva Dilnoza Maxsudjonovna; Axmedova Parvina Abdumanonovna (International Journal of Innovations in Engineering Research and Technology, 2021)
Fromthis article we see that philology is a kind of complex of sciences, " a combination, a community of humanities -linguistic, literary, historical, that study the history and essence of the spiritual culture of mankind through the linguistic and stylistic analysis of written text